Exposition Internationale du Surréalisme 1959-1960. - Arp, Hans, Jean; Bellmer, Hans; Benayoun, Robert; Benoît, Jean; Bounoure, Vincent; Breton, André; Bédouin, Jean-Louis; Cabanel, Guy; Carrington, Leonora; Debout, Simone; Doumayrou, Guy; Duprey, Jean-Pierre; et al. (Paris : Galerie Daniel Cordier, 1959)
Arp, Hans (Jean) ; Baj, Enrico ; Bellmer, Hans ; Benayoun, Robert ; Bona ; Brauner, Victor ; Carrington, Leonora ; Copley, William ; Dax, Adrien ; Duchamp, Marcel ; Elléouet, Yves ; Ernst, Max ; Garnier, Jules-Arsène ; Gette, Paul-Armand ; Giacometti, Alberto ; Granell, E.F. ; Van Hecke, Roger ; Heisler, Jindrich ; Herold, Jacques ; Hiquily, Philippe ; Johns, Jasper ; Kalinowski, Horst Egon ; Lagarde, Robert ; Laloy, Yves ; Lam, Wifredo ; Lebel, Jean-Jacques ; Lombard, J.-B. ; Magritte, René ; Man Ray ; Manina ; Maréchal ; Maria ; Matta (Roberto Antonio Sebastian Matta Echaurren) ; Mesens, E.L.T. ; Miro, Joan ; Müller, Robert ; Oelze, Richard ; Oppenheim, Meret ; Paalen, Wolfgang ; Parent, Mimi ; Péret, Benjamin ; Picasso, Pablo ; Rauschenberg, Robert ; Schröder-Sonnenstern, Friedrich ; Styrsky, Jindrich ; Svanberg, Max Walter ; Tanguy, Yves ; Toyen ; Zurn, Unika
biog.
Frans
Exposition Internationale du Surréalisme 1959-1960, Galerie Daniel Cordier, Paris, 15 décembre 1959 - 29.01.1960
boek